2005
DOI: 10.1161/01.atv.0000158307.66945.b4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Signaling in Arteries Prevents Smooth Muscle Apoptosis

Abstract: Objective-Insulin is an antiapoptotic factor of cultured vascular cells, but it is not clear whether it also exerts antiapoptotic effects on vascular cells in vivo. We studied insulin receptor signaling in the arteries of normal and diabetic rats to establish whether insulin exhibits antiapoptotic activity toward vascular smooth muscle cells in vivo as well as in vitro. Methods and Results-Western blot analysis and real-time polymerase chain reaction revealed ␣-and ␤-subunits of the insulin receptor in associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Thus, the simultaneous insult of hyperglycaemia and hyperlipidaemia induced formation of matrix vesicles and of apoptotic bodies that both may serve as calcification matrices. These results complete earlier observations that under diabetic conditions SMCs were more susceptible to cell death, a condition to which additional apoptosis-inducing factors contribute, such as AGEs and free radicals (Nakazawa et al, 2005).…”
Section: Smcs Dysfunction In Hyperlipidaemia: Migration and Proliferasupporting
confidence: 90%
“…Thus, the simultaneous insult of hyperglycaemia and hyperlipidaemia induced formation of matrix vesicles and of apoptotic bodies that both may serve as calcification matrices. These results complete earlier observations that under diabetic conditions SMCs were more susceptible to cell death, a condition to which additional apoptosis-inducing factors contribute, such as AGEs and free radicals (Nakazawa et al, 2005).…”
Section: Smcs Dysfunction In Hyperlipidaemia: Migration and Proliferasupporting
confidence: 90%
“…MMPs represent a marker of vascular disease (Maxwell et al 2001), as was also demonstrated by our group in children and adolescents with type-1 diabetes (Derosa et al 2004) and in patients with hypertension (Derosa et al 2006) and pathological conditions associated with chronic endothelial dysfunction and unstable plaque formation (Nakazawa et al 2005).…”
Section: Discussionsupporting
confidence: 55%
“…Insulin exerts antiapoptotic effects in macrophages, endothelial cells, and smooth muscle cells in vitro. [61][62][63] During phagocytosis of apoptotic cells, both PI3K/ AKT 64,65 and MEK/ERK [65][66][67] signaling cascades in normal phagocytic macrophages are involved. Further research is needed to determine whether engulfment of apoptotic cells by macrophages is altered in type 2 diabetes.…”
Section: Potential Mechanisms: Role Of Macrophage Apoptosis and Phagomentioning
confidence: 99%